2021
DOI: 10.1136/ijgc-2021-002692
|View full text |Cite
|
Sign up to set email alerts
|

Refusal of surgery and survival outcomes in endometrial cancer

Abstract: ObjectivesThe goal of this study was to determine the impact refusal of surgery has on overall survival in patients with endometrial cancer.MethodsFrom January 2004 to December 2015, the National Cancer Database was queried for patients with pathologically proven endometrial cancer who were recommended surgery and refused. Inverse probability of treatment weighting was used to account for differences in baseline characteristics between patients who underwent surgery and those who refused. Kaplan–Meier analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Black women and those with the lowest high school graduation rate were more likely to refuse surgery for gynecological cancer, for example [69]. These observations were confirmed in other studies focusing on patients with endometrial cancer who refused surgical treatment [70,71]. Black (RR 2.9; 95% CI 2.1-4.1) and Hispanic (RR 2.0; 95% CI 1.2-3.1) women were more likely to refuse surgery when compared with White patients [71].…”
Section: Fertility-sparing Treatment Vs Less Radical Treatment: Treat...supporting
confidence: 66%
“…Black women and those with the lowest high school graduation rate were more likely to refuse surgery for gynecological cancer, for example [69]. These observations were confirmed in other studies focusing on patients with endometrial cancer who refused surgical treatment [70,71]. Black (RR 2.9; 95% CI 2.1-4.1) and Hispanic (RR 2.0; 95% CI 1.2-3.1) women were more likely to refuse surgery when compared with White patients [71].…”
Section: Fertility-sparing Treatment Vs Less Radical Treatment: Treat...supporting
confidence: 66%
“…EC is treated primarily by surgery, with clinical risk factors determining whether adjuvant radiotherapy or chemotherapy should be administered 4 . The survival rate for patients with EC who refused surgery was only 29.2% 22 . Lymph node involvement is an important prognostic factor in patients with EC 23 .…”
Section: Discussionmentioning
confidence: 99%
“… 4 The survival rate for patients with EC who refused surgery was only 29.2%. 22 Lymph node involvement is an important prognostic factor in patients with EC. 23 Our study also found that most patients with lymph node metastasis died of EC.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, the treatment technology of EC has made great progress, especially for patients with early EC, and the 5-year survival rate has been greatly improved [19,20]. However, for advanced EC patients, the survival rate is often reduced due to the existence of chemoresistance [21,22].…”
Section: Discussionmentioning
confidence: 99%